Thyroid axis hormones and anthropometric recovery of children/adolescents with overweight/obesity: A scoping review - Urrea, Carlos Ramos; Pedroso, Amanda Paula; Thomazini, Fernanda; Carmo, Andreia Cristina Feitosa do; Telles, Mônica Marques; Sawaya, Ana Lydia; Franco, Maria do Carmo Pinho; Ribeiro, Eliane Beraldi (Frontiers in Nutrition, 2023)
Thyroid hormones exert multiple physiological effects essential to the maintenance of basal metabolic rate (BMR), adaptive thermogenesis, fat metabolism, growth, and appetite. The links between obesity and the hormones of the thyroid axis, i.e., triio-dothyronine (T3), thyroxine (T4), and thyrotropin (TSH), are still controversial, especially when considering children and ado-lescents. This population has high rates of overweight and obesity and several treatment approaches, including nutritional, psy-chological, and physical exercise interventions have been used. Understanding the importance of the hormones of the thyroid axis in the recovery from overweight and obesity may help directing measures to the maintenance of a healthy body composi-tion. The present scoping review was carried out to analyze studies evaluating these hormonal levels throughout interventions directed at treating overweight and obesity in children and adolescents. The main purpose was to ascertain whether the hor-mones levels vary during weight loss. We selected for analysis 19 studies published between 1999 and 2022. Most of the studies showed that changes in different anthropometric indicators, in response to the multidisciplinary interventions, correlated posi-tively with free T3 (fT3), total T3 (TT3), and TSH. With respect to free T4 (fT4) and total T4 (TT4), the most common finding was of unchanged levels and, hence, no significant association with weight loss. Moreover, thyroxine supplementation has failed to affect the response to the interventions. Further studies are necessary to elucidate the relevance of the variations in hormone levels to the establishment of overweight/obesity and to the recovery from these conditions in children/adolescents.